Analysis of the Utilization of Social Media as a Means of Learning Elementary School Students in the Digital Era - Afifa, Khaulah; Tri Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the trends in elementary school teachers' teaching practices within thematic learning, using social media as a supporting tool for learning activities in the digital era. The research method used is library research, with data sources coming from academic journals, official books, and previous studies related to social media-based learning. Data was collected through library analysis and content analysis of various publications discussing the role of social media in basic education. The findings show that social media platforms like Facebook, WhatsApp, and YouTube are widely used by elementary school teachers to enhance thematic materials, expand learning resources, and create more dynamic interactions between teachers, students, and parents. The integration of social media also contributes to increased student creativity and motivation. However, the main challenges identified include limited digital literacy among teachers and a lack of educational technology training. Overall, social media has significant potential as an innovative and timely approach to thematic learning that adapts to current developments.